Weed control in distress – can all weeds still be controlled with herbicides in future? - Drobny, Hans G. (Julius-Kühn-Archiv, 2016)
The introduction and availability of highly active and selective herbicides in all important field crops, in the last decades, enabled the simplification and money saving in crop rotations and agronomic measures. This resulted in respective specialized and adapted weed populations, and consequently an increasing selection of resistant populations. Since the introduction of the ALS-inhibitors (starting 1985) and the 4-HPPD-inhibitors (2001), no new MoA-Classes were registered, and there are none in the registration process. Several established herbicides were not registered or re-registered in the EU, or were severely restricted in their application. The cost and the risk to develop and register a new selective herbicide in the EU are hardly justified, in relation to their market potential. The only solution on problem fields, with resistant populations, is to change the agronomic practices, like crop rotation, soil tillage, seeding time, etc., as a precautionary principle also on still „normal“ fields. The different advising institutions have to integrate these aspects into their recommendations, besides the proper herbicide management.